Atrazine and malathion shorten the maturation process of Xenopus laevis oocytes and have an adverse effect on early embryo development. (April 2016) - Ji, Qichao; Lee, Jessica; Lin, Yu-Huey; Jing, Guihua; Tsai, L. Jillianne; Chen, Andrew; Hetrick, Lindsay; Jocoy, Dylan; Liu, Junjun
Abstract: The use of pesticides has a negative impact on the environment. Amphibians have long been regarded as indicator species to pollutants due to their permeable skin and sensitivity to the environment. Studies have shown that population declines of some amphibians are directly linked with exposure to agricultural contaminants. In the past, much of the studies have focused on the toxic effect of contaminants on larvae (tadpoles), juvenile and adult frogs. However, due to the nature of their life cycle, amphibian eggs and early embryos are especially susceptible to the contaminants, and any alteration during the early reproductive stages may have a profound effect on the health and population of amphibians. In this study, we analyzed the effect of atrazine and malathion, two commonly used pesticides, on Xenopus laevis oocyte maturation and early embryogenesis. We found that both atrazine and malathion shortened the frog oocyte maturation process and resulted in reduced Emi2 levels at cytostatic factor-mediated metaphase arrest, and a high level of Emi2 is critically important for oocyte maturation. Furthermore, frog embryos fertilized under the influence of atrazine and/or malathion displayed a higher rate of abnormal division that eventually led to embryo death during early embryogenesis. Highlights: Atrazine and malathion shortened the maturation process of Xenopus oocytes. Atrazine and malathion caused a reduction of Emi2 level in matured Xenopus oocytes. Atrazine and malathion caused a higher death rate during Xenopus early embryogenesis. The toxic effects of pesticides on Xenopus oocytes and embryos were dose dependent. A pesticide mixture had a more significant effect than an individual pesticide.